(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
In this research, measurement of radioactivity of bismuth-212 in the soil of the village of the Ien Lailonin- Alhafah area- Latakia city using gamma spectrometry to make sure the radioactive content to soil, and was measuring the radioactivity of bismuth-212 using the alpha spectroscopy, after digestion 10g of soil using nitric acid and sulfuric acid concentrated, and then spontaneaous deposition into high purity a silver disc. the results show that: the radioactivity of bismuth-212 (1,48Bq) using gamma spectrometry and (2,05Bq)using the alpha spectroscopy It is within the range allowed international border ,taking into account the errors in measurements.